Transcranial Color-Coded Doppler Cerebral Hemodynamics Following Aerobic Exercise Training: Outcomes From a Pilot Randomized Clinical Trial. Issue 3 (September 2022) - Mitchell, Carol; Gaitán, J. Max; Pewowaruk, Ryan J.; Gepner, Adam D.; Hess, Timothy; Wilbrand, Stephanie M.; Dempsey, Robert J.; Dougherty, Ryan J.; Cook, Dane B.; Okonkwo, Ozioma
Introduction: An active lifestyle with regular exercise is thought to decrease or delay the onset of Alzheimer dementia through increasing blood flow to the brain. We examined the mean flow velocity (MFV) and pulsatility index (PI) in the middle cerebral arteries of individuals randomized into 2 groups—a usual physical activity (UPA) group and an enhanced physical activity (EPA) exercise intervention group—to determine whether exercise training is related to changes in cerebral blood flow. Methods: We examined 23 participants, randomized into a UPA group (n = 12) and an EPA group (n = 11), with transcranial color-coded Doppler (TCCD) and cardiorespiratory fitness (VO2 peak) testing at baseline and following a 26-week intervention. Transcranial color-coded Doppler was used to measure MFV and PI. Participants in the EPA group completed supervised aerobic exercise training for 26 weeks. Kendall's tau-b correlation was used to examine relationships between variables. The Wilcoxon rank-sum tests were used to examine changes between the UPA and EPA groups. Results: There was no significant change in MFV or PI in the UPA group or the EPA group ( P values >.05) between baseline and 26 weeks; the change between the UPA and EPA groups was also not significant ( P = .603). There was no evidence of an association between change in VO2 peak and change in MFV or PI (all P values >.05). Participants in the EPA group significantly increased their VO2 peak compared with the UPA group ( P = .027). Conclusion: This study did not demonstrate evidence of a significant change in the MFV in the middle cerebral arteries or evidence of a significant change in the PI between UPA and EPA groups. Future studies should be performed in larger cohorts and should consider use of personalized exercise programs to maximize understanding of how cerebrovascular hemodynamics change in structure and function with exercise for adults at risk of Alzheimer dementia.